6x2 + 10x = 2x*(3x + 5)
4x-3+6x+3 4x+6x=10x -3+3=0 10x is the answer!
It is a quadratic expression in the variable x.
We know that when you submit questions you aren't free to use the right format to make the mathematical terms crystal clear. It is likely that you mean "x squared times 6 plus x squared times 2", which is clearer. You can factor out the "x squared" and you will see that you get "x squared times 8". You COULD mean (6x) squared plus (2x) squared, which would be different. 6x times 6x would equal x squared times 36, so your answer will be much different.
-3x + 10x = 7x3x + 3x = 6x
It is: 10x+14 simplified
4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)
4x2+10x+6x+15 is the same as 4x2+16x+15 = (2x+5)(2x+3) when factored
6x+58=10x+14 first move the 58 to the other side by subtracting it. 6x=10x-48 Then you move the 10x to the other side by subtracting it. -4x=-48 Then you divide both sides by -4 x=12 is you answer.
Assuming you mean x squared plus 5x squared... the answer is 6x squared.
10x + 7 = 4x + 49 6x + 7 = 49 6x = 42 x = 6